The effectiveness of investigation group learning model based on Marzano’s instructional framework in improving students’ higher order thinking skill - Yeyen Suryani; Sapriya Sapriya; Elly Malihah; Kokom Komalasari (Edusentris, 2020)
This study aims to analyze the effectiveness of investigation group learning model based on Marzano’s instructional framework in improving students’ higher order thinking skills. The method used in this study was a quasi-experimental method with the matching only control group pretest-posttest design. Here, the data were collected through observations, questionnaires, and tests. The tests consisting of limited and extensive tests aim to analyze the effectiveness of the investigation group learning model based on Marzano’s instructional framework in improving students’ higher order thinking skills. The results showed that the majority of students (>75%) have an increased level of higher order thinking skills (critical and creative thinking skills). It was proved by the results of statistical analysis where the sig. value < 0.05 and ttable > tcount. Thus, H0 is rejected meaning that there is a significant difference on students’ higher order thinking skills before and after applying the investigation group learning model based on Marzano’s instructional framework in the teaching and learning process. Then, if it is classified, the improvement of students’ critical and creative thinking skills is included into the medium category. Hence, it can be concluded that the investigation group learning model based on Marzano’s instructional framework is effective in improving students’ higher order thinking skills in social studies learning.